Enter into society: Digitalized livelihoods and prosumer labor for people with disabilities in China - Bao, Yaxiong; Hu, Xinyu; Zhang, Ruijie; Shi, Xiaochuan (Frontiers in Psychology, 2023)
Background The current debates on “digital labor” focus on a gorgeous and comprehensive experiential description and theoretical exposition but do not provide a thorough examination of the unique context and social structure. In China, the development of internet is closely tied to politics, the Chinese Government uses internet as a tool of social governance. More importantly, aside from desire-based communications produced by corporate ideology, the Chinese people’s passion for the Internet also comes from individual survival, especially the middle and lower class of information represented by the disabled people. This means that analysis of the digital labor among people with disabilities in China must be done from a variety of angles, including politics, society and culture. Methods This study combines life-history interviews and field research methods to explore the value and significance of digitalized livelihoods and free prosumer labor for people with disabilities in China through self-narration. Since 2020, researchers have been volunteering at two social organizations serving people with physical disabilities in Wuhan city, Hubei Province. We participated in 26 assistance activities for disabled groups which included three 14-day training camps, and interviewed 40 people with physical disabilities. Results This study found that although the digitalized livelihoods practice of people with disabilities is still “precarious labor” in nature, whose self-expression in the cyberspace is easy to fall into the shackles of capital flow logic. However, digital labor practice provides them with the opportunity to “sit at home, enter the community and society,” also enables them to “live independently.” More importantly, this opportunity and possibility enable people with disabilities to experience a sense of value and self-esteem as “competent people.” Therefore, in the realistic environment of structural obstacles in the social life of the people with disabilities in China, the possibility of “inclusiveness” brought by digital labor is the core value brought by digital society.